The appeal : a novel - Hallett, Janice (Atria Books, 2022)
"Welcome to Lockwood, proud home of The Fairway Players, who, under the creative control of Martin Hayward, the owner of the local country club, are putting on a production of Arthur Miller's "All My Sons." The star, as always: Martin's wife, Helen, the only person in the troupe with any real acting talent. But this is not a production like any other: just as rehearsals get under way, tragedy strikes: Poppy Reswick, Martin and Helen's beloved granddaughter, is diagnosed with a rare form of cancer. An experimental treatment is available from the US - at a massive cost. The Players and the entire town rally in order to raise the 250,000 pounds needed to give Poppy a chance at survival. Not everybody is convinced that the experimental treatment is all it's cracked up to be, however. First among the doubters is Sam Greenwood, who has only recently moved to Lockwood with her husband, Kel, after spending several years as an NGO worker in Sub-Saharan Africa. Are her suspicions justified? Or does she merely have an axe to grind with the doctor who's looking after Poppy? The tension within the community is palpable, and on the night of the Players' dress rehearsal, things come to a head. The next day, a dead body is found, and soon afterwards, an arrest is made. In the run-up to the trial, two law students find themselves sifting through the evidence in the form of e-mails, texts, and letters, trying to make sense of it all and unmask the real killer"--